Characterisation of the function of ADP-ribosylation factor-like 4D (Arl4D) in myogenesis. - Lee, Jonathan Houjin. (2009)
Myogenesis is the process by which muscle regenerates itself. It is regulated by a number of genes, which include peroxisome proliferator-activated receptor (PPAR) δ. In a recent microarray study, it was found that ADP-ribosylation factor-like 4D (Arl4D) got up-regulated upon treatment of myotubes with a PPARδ agonist. To date, the function of Arl4D in myogenesis has not been studied. Here we show that Arl4D is expressed at higher levels in the soleus compared to other hind limb muscles. Using the C2C12 myoblast cell line, we show that Arl4D may be a downstream target of PPARδ and aids in the PPARδ driven muscle fibre type switch. We also show that Arl4D is post-transcriptionally regulated and its expression is markedly increased during myoblast differentiation. Over expression of Arl4D enhances both the proliferation and differentiation of C2C12 myoblasts. Taken together, these findings suggest a vital role for Arl4D in myogenesis. They also open up several interesting avenues of inquiry, which may lead to the eventual development of therapies to treat a number of myopathies.